Evaluasi Usability Penggunaan Aplikasi GoPay dan DANA Menggunakan Heuristik Evaluation - Naily Iqomatar Rosyidah; Mardiana Andarwati (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The rapid growth of digital wallet application usage in Indonesia demands high levels of usability, as interface errors can directly impact user security and trust. This study aims to evaluate and compare usability issues in the GoPay and DANA applications using the Heuristic Evaluation method based on Nielsen’s ten principles, focusing on findings with high severity levels (Severity Rating 3). This research employs a descriptive qualitative approach involving three evaluators who performed evaluations based on primary usage scenarios, such as top-ups, fund transfers, payments, and account settings. The evaluation results indicate that GoPay has six findings classified as Major Usability Problems, while DANA has three findings with the same severity level. Critical issues in GoPay primarily relate to a lack of system status transparency, high user cognitive load, limited efficiency in search features, and weak support for help and error handling. Meanwhile, critical findings in DANA include unclear transaction status, inconsistent placement of security features, and a lack of diagnostic feedback during input errors. Comparative analysis shows that although both applications face similar usability problems across several heuristic principles, the characteristics of these weaknesses and their impact on user experience differ. Based on these findings, this study proposes usability improvement recommendations prioritized for high-severity principles to enhance efficiency, convenience, and user trust in utilizing digital wallet applications.